ACCUMULATION OF CHROMIUM (CR) AND LEAD (PB) IN FRUIT TREES GROWN IN HEAVY METAL-POLLUTED AND ECOLOGICALLY CLEAN AREAS OF TASHKENT REGION (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
The accumulation of heavy metals in the organs (leaves, branches, fruits, seeds) of fruit trees growing in areas of Tashkent region contaminated with heavy metals and ecologically clean areas was studied. According to the results of the study, the accumulation of lead and chromium in the organs of fruit trees follows the following decreasing sequence: leaf → stem → seed / grain →fruit.